2019
DOI: 10.31235/osf.io/ecjxy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conditional Families and Lesbian, Gay, Bisexual, Transgender, and Queer Youth Homelessness: Gender, Sexuality, Family Instability, and Rejection

Abstract: Existing research on lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth home- lessness identifies family rejection as a main pathway into homelessness for the youth. This finding, however, can depict people of color or poor people as more prejudiced than White, middle-class families. In this 18-month ethnographic study, the author complicates this rejection paradigm through documenting the narratives of 40 LGBTQ youth experienc- ing homelessness. The author examines how poverty and family instability… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 38 publications
(43 reference statements)
1
34
1
Order By: Relevance
“…In a qualitative study with 90 parents and 90 LGB children (ages 15–24), with 59% of the sample an ethnic minority, Black, Hispanic, and Latino parents report more parental rejection of their children and more homonegativity than White parents, with children corroborating these results (Richter, Lindahl, & Malik, ). In an ethnographic and in‐depth interview study with 40 lesbian, gay, bisexual, transgender, and queer youth, Robinson () showed how families who were already economically disadvantaged experienced additional instability when a child was gender nonconforming, leading to increases in adolescent and young adult poverty and homelessness. Considerably more research needs to address what might be unique stressors—or sources of resilience—for SGM youth and adults of color and across the socioeconomic spectrum within their family‐of‐origin relationships.…”
Section: Critiques and Future Researchmentioning
confidence: 99%
“…In a qualitative study with 90 parents and 90 LGB children (ages 15–24), with 59% of the sample an ethnic minority, Black, Hispanic, and Latino parents report more parental rejection of their children and more homonegativity than White parents, with children corroborating these results (Richter, Lindahl, & Malik, ). In an ethnographic and in‐depth interview study with 40 lesbian, gay, bisexual, transgender, and queer youth, Robinson () showed how families who were already economically disadvantaged experienced additional instability when a child was gender nonconforming, leading to increases in adolescent and young adult poverty and homelessness. Considerably more research needs to address what might be unique stressors—or sources of resilience—for SGM youth and adults of color and across the socioeconomic spectrum within their family‐of‐origin relationships.…”
Section: Critiques and Future Researchmentioning
confidence: 99%
“…A further challenge that LGBTQ+ homeless youth face is family conflict that has been consistently shown to be a major factor leading to homelessness. The negative consequences of 'coming out' to family members and friends can include hostility, abuse, rejection and eventual ejection from the family home (Robinson 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, B. A. Robinson () has argued that conditional families are those in which “certain terms or conditions related to gender and sexuality had to be met for the youth to be a part of the family” (p. 387). He argued that this framework adds clarity to the emotional implications of offering family support contingent upon certain conditions, and particularly of “the conditions of poverty and family instability [and] the larger social conditions that shape the experiences of some LGBTQ youth” whose families marginalize them (p. 387).…”
Section: Discussionmentioning
confidence: 99%